2001
DOI: 10.1007/s001250051593
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed coeliac disease and risk of autoimmune disorders in subjects with Type I diabetes mellitus

Abstract: AIMS/HYPOTHESIS: We tested the hypothesis that silent coeliac disease is more frequent than expected in both patients with Type I (insulin-dependent) diabetes mellitus and their first-degree relatives. We evaluated how the presence of other autoimmune disorders in diabetic patients and their first-degree relatives is related to silent, unrecognized coeliac disease. METHODS: Sera from 491 subjects with Type I diabetes, 824 relatives and 4,000 healthy control subjects were screened for anti-endomysial antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 19 publications
(22 reference statements)
5
79
1
4
Order By: Relevance
“…The higher proportion of children with diarrhea may be related to the younger age at diagnosis reported in their study of 6.5 years, since classical CD tends to present more in the younger age group. Patients with asymptomatic CD, however, are still at risk of complications such as autoimmunity1011 and small-bowel malignancies 12…”
Section: Discussionmentioning
confidence: 99%
“…The higher proportion of children with diarrhea may be related to the younger age at diagnosis reported in their study of 6.5 years, since classical CD tends to present more in the younger age group. Patients with asymptomatic CD, however, are still at risk of complications such as autoimmunity1011 and small-bowel malignancies 12…”
Section: Discussionmentioning
confidence: 99%
“…More often, CD is diagnosed shortly after or sometimes years after the onset of type 1 diabetes. 5,[21][22][23] To determine the temporal relationship between the onset of type 1 diabetes and CD, we tested for anti-tTG in the initial serum taken at the onset of diabetes using our serum library. The retroactive screening showed that only 1 of 11 patients (patient 11)-the one with a positive jejunal biopsy-was anti-tTG negative at the onset of the type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Low to moderately positive IgA tTG levels should be interpreted in the context of symptoms and, in many instances, should be followed with repeat IgA tTG testing every 6 -12 months (199). Many children with type 1 diabetes who have elevated tTG levels are either asymptomatic or have subtle gastroenterologic symptoms (208,209). A small-bowel biopsy may be recommended in patients with positive tTG, even in the absence of symptoms, to confirm the diagnosis of celiac disease.…”
Section: Type 1 Diabetes In Children and Adolescentsmentioning
confidence: 99%